Combination of metformin and luteolin synergistically protects carbon tetrachloride‐induced hepatotoxicity: Mechanism involves antioxidant, anti‐inflammatory, antiapoptotic, and Nrf2/HO‐1 signaling pathway. (23rd July 2019) - Yan, Yang; Jun, Chen; Lu, Yang; Jiangmei, Song
Abstract: Liver diseases are one of the fatal disorders due to the vital role of the liver. Carbon tetrachloride (CCl4 ) is the most perceived chemical substance utilized in developing models of hepatic damage. Metformin (Met) is a potent antidiabetic and redox modulatory agent that has shown anticancer and protective effects on various organs. Therefore, addition of therapy with natural antioxidative agents or herbal extracts shows defensive impacts against different injuries inside the body. Luteolin (Lut) can be found in several customary Chinese remedies. It has been reported for various pharmacological actions such as antitumor, antioxidative, and anti‐inflammatory impacts. Here, the liver injury rat model was established using CCl4 (1.00 mL/kg body weight) in vivo. The protective roles of Met and Lut separately or in combination were observed in hepatotoxicity induced by CCl4 . The result was shown that both Met and Lut, while individually used, were normally active in diminishing CCl4 ‐caused hepatotoxicity. The combination of two drugs performed synergistically to improve liver damage caused by CCl4, as shown by the considerably improved liver dysfunction. Met and Lut showed highly antioxidative effects on CCl4 ‐treated rats moderately by increasing the activities and expression of the antioxidant enzymes. Along with this, a combination of Met and Lut significantly suppressed inflammatory responses, which is evidenced by the reduced level of inflammatory cytokines together with interleukin 1 beta (IL‐1β), tumor necrosis factor alpha (TNF‐α), and interleukin 6 (IL‐6). Additionally, CCl4 ‐agitated apoptosis was intensely reduced by Met and Lut through reducing cleaved caspase‐3 and Bax (pro‐apoptotic factor) while increasing Bcl‐2 (antiapoptotic factor) signaling pathways. Cotreatments of Met and Lut upregulated nuclear factor erythroid 2‐related factor 2 (NRF2) and heme oxygenase‐1 (HO‐1) expression in the CCl4 ‐intoxicated rat's liver. The above result recommended that combination of Met and Lut may have a substantial potential and synergizing impact against CCl4 ‐induced hepatotoxicity.